Iron-Modification of Pyroclastic Material from PCCVC Eruption (Chile): Characterization and Application to Remove Arsenic from Groundwater - González, María José (2015)
Pyroclastic material from the PCCVC eruption (Chile) was modified with iron (III) solutions leading to the formation of ferrihydrite surface deposits. The aim of the chemical treatment was to prepare an adsorbent to remove arsenic from water by using low-cost mineral wastes. Physicochemical characterization of original and modified materials was carried out by XRD, BET-N2 adsorption, SEM-EDS microscopy and ICP-AES chemical analysis. The modified ash revealed that the increase of bulk iron content was close to 5% (expressed as Fe2O3) whereas surface values were 20.6% Fe2O3. Surface properties showed an increase of BET specific surface with prevalence of mesopores and an increase of total pore volume attributed to presence of nanoscopic iron phase. Kinetic and equilibrium studies were directed to optimize the operative conditions related to the material adsorptive capacity for removing arsenate species. Hence, the adsorbent dose, contact time, pH, stirring and sedimentation were evaluated in batch process. The optimal adsorption dose was 40 g・L−1 and the solid-liquid contact time was stirring (1 h) and sedimentation (23 h), enough to ensure an adequate turbidity value valid for a pH range between 3.77 and 8.95. The analysis of the isotherm equilibrium by using the Langmuir linear method showed a R2 = 0.995 value. The performance of the treatment to remove arsenic by using a cost-effective adsorbent prepared from volcanic material is a promising technology to apply in the environmental field.